2003
DOI: 10.1002/asi.10291
|View full text |Cite
|
Sign up to set email alerts
|

An emerging view of scientific collaboration: Scientists' perspectives on collaboration and factors that impact collaboration

Abstract: Collaboration is often a critical aspect of scientific research, which is dominated by complex problems, rapidly changing technology, dynamic growth of knowledge, and highly specialized areas of expertise. An individual scientist can seldom provide all of the expertise and resources necessary to address complex research problems. This paper describes collaboration among a group of scientists, and considers how their experiences are socially shaped. The scientists were members of a newly formed distributed, mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
316
0
17

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 346 publications
(355 citation statements)
references
References 30 publications
10
316
0
17
Order By: Relevance
“…In addition, studies in this general class have found and analyzed patterns in these co-authorships, leading to findings that, for example, confirm Crane's (1972) notion of the invisible college of geographically distributed researchers well known to each other (D. J. d. S. Price, 1986), and the presence of intellectual centers in the global scientific arena (Luukkonen, 1992). In some cases, such centers are rendered explicit through the establishment of distributed multidisciplinary research centers that foster collaboration (Hara, Solomon, Kim, & Sonnenwald, 2003).…”
Section: General Studies Of Scientific Collaborationmentioning
confidence: 69%
See 1 more Smart Citation
“…In addition, studies in this general class have found and analyzed patterns in these co-authorships, leading to findings that, for example, confirm Crane's (1972) notion of the invisible college of geographically distributed researchers well known to each other (D. J. d. S. Price, 1986), and the presence of intellectual centers in the global scientific arena (Luukkonen, 1992). In some cases, such centers are rendered explicit through the establishment of distributed multidisciplinary research centers that foster collaboration (Hara, Solomon, Kim, & Sonnenwald, 2003).…”
Section: General Studies Of Scientific Collaborationmentioning
confidence: 69%
“…Evidence from a limited set of studies suggest that there is a positive relationship between email usage and remote collaboration (Cohen, 1996;Walsh & Bayma, 1996;Walsh, Kucker, & Maloney, 2000;Walsh & Maloney, 2002), but this question remains to be definitively answered. Hara, et al (2003) (Watson, 1968), but these do not likely represent the modal experience of scientists in collaborations.…”
Section: General Studies Of Scientific Collaborationmentioning
confidence: 99%
“…Given the relative strength of the development of US and China nanotechnology, taking the two-sided nature of research collaboration beyond quid pro quo (Hara, Solomon, & Sonnenwald, 2003) into consideration, it is highly possible that only the most promising research of CKMs is recognized or acknowledged by US collaborators, which contributes to the widening gap between international and non-international collaboration at the individual CKM level.…”
Section: Fixed Effects or Random Effectsmentioning
confidence: 99%
“…Many researchers have noted that the need to gain access to instruments, unique data, and funding for increasingly complex projects requires the assemblage of individuals and teams with diverse skills [2] . As many scientists become more and more highly specialized, these teams are necessary to solve complex problems.…”
Section: Information Practices Across the Biological Sciencesmentioning
confidence: 99%